EFEKTIFITAS EPHEDRINE 20 μg/KgBB DIBANDINGKAN DENGAN LIDOKAIN 30 mg TERHADAP NYERI DAN RESPON HEMODINAMIK AKIBAT PENYUNTIKAN PROPOFOL PADA ANESTESIA UMUM DENGAN INTUBASI ENDOTRAKEA - Dody Firmanda (Jurnal Penelitian Farmasi & Herbal, 2019)
Purpose: To determine the effectiveness of pain reduction and hemodynamic response using a 30 mg lidocaine and 20 μg/kg of BB in the thirty seconds before propofol induction in general anesthesia with endotracheal intubation. Methods: This study has a double-blind clinical test design. A total of 140 ASA-1 and ASA-2 patients who would undergo surgery with general anesthesia techniques used propofol induction and were taken by Endotraskea to obtain one of the two groups. Thirty seconds before propofol induction, the group I is by adding lidocaine 30 mg, while the group II is by adding the ephedrine 20μg/KgMW thirty seconds before propofol induction. Assess the value of VAS at the time of injection of the first three cc propofol with an injection speed of 15-18 seconds. Systolic, diastolic blood pressure, MAP, and heart rate are recorded before premedication (baseline), after premedication, after administration of ephedrine, after induction of propofol and the 1st minute, 3.5 after intubation. Statistical tests conducted with Chi-Square, Mann-Whitney, and Independent T-Test tests. Result: The comparison of the pain incidence rate between the two groups is the same as the value of VAS 0-3 in both groups. Indicate a meaningful difference in the ephedrine group 20 μg/KgMW obtained a median value of visual analog scale 0, 64.3% while VAS 1-3 as much as 35.7% in group Lidocaine 30 mg obtained by the median value of visual analog scale 0, 47.1% While at VAS 1-3 as much as 52.9%. The average arterial pressure of the ephedrine group is 30 seconds after the injection of propofol, 83 (73-91) mmHg, which is significantly higher when compared with the average arterial pressure of the group Lidocaine 30 mg, 74 (68-85) mmHg. Arterial pressure at 1, 3, and 5 min after intubation in the ephedrine group consistently demonstrated a significantly higher value than the arterial pressure of the lidocaine group. Conclusion: Ephedrine 20 μg/KgMW and 30 mg lidocaine are equally effective in terms of pain reduction due to propofol induction. Ephedrine 20 μg/KgMW provides a lesser effect of hemodynamic changes in the injection of general anesthesia with endotracheal intubation.